Pengaruh Intensitas Penggunaan Media Sosial Instagram Terhadap Kreativitas Mahasiswa Fisip Universitas Pancasakti Tegal - Aulia Qurota A’yun; Sarwo Edy; Diryo Suparto (Institut Nalanda, 2023)
The development of communication science and technology is advancing rapidly in the current era of globalization. Various innovations and technologies have been utilized to facilitate human activities through social media. Communication has become a vital necessity for all individuals, regardless of age, gender, occupation, or social status. Post the industrialization era, we are now entering the information age. This research aims to evaluate the influence of Instagram social media usage intensity on the creativity of students at the Faculty of Social and Political Sciences, Pancasakti University, Tegal. The study adopts the New Media theory with a quantitative approach. The research population consists of students from the 2017 and 2018 cohorts, with a sample of 75 respondents selected using purposive sampling techniques. Data collection was conducted through questionnaires. The research findings indicate a positive relationship between Instagram social media usage intensity and student creativity, as evidenced by the calculation of t-test > t-table (12.265 > 1.999). The influence of social media usage intensity in this study is 67.3%, while the remaining 32.7% is influenced by other factors.